Eric Murray and Cecil Murray interviewed by Chris Sullivan in the Chris Sullivan folklore collection - Murray, Eric, 1918-1995.; Murray, Cecil -1995.; Sullivan, Chris (Christopher Daniel), 1953- (1987)
Folkloric recording.
Recorded on 14 July 1987, at Bunyah, N.S.W.
Digital master available
Keywords: Murray, Eric, -- 1918-1995 -- Interviews; Murray, Cecil, -- -1995 -- Interviews; Folk musicians -- New South Wales -- Bunyah -- Interviews; Folk dance music -- New South Wales -- Bunyah; Folk music -- New South Wales -- Bunyah; Violin music; Accordion music; Folk musicians